Pulmonary Tuberculosis and Lung Abscess: A Case Report - Alifyah Alza Adawiya Latuconsina; Erlin Syahril; Dwi Anggita (International Medical Journal Corp. Ltd, 2025)
A 49-year-old woman presented to the hospital with a chief complaint of dyspnea that began in the morning. She reported a history of hemoptysis, initially manifesting as clots equivalent to approximately one tablespoon, which has since diminished to blood-streaked sputum. A notable episode of hemoptysis had occurred one year prior, for which she was prescribed Anti-Tuberculosis Treatment (ATT). The patient has experienced a chronic cough since the previous year, with associated dyspnea during severe coughing episodes. She also reported intermittent fever. A thoracic examination revealed a normochest configuration with symmetric respiratory movements. Palpation identified decreased tactile fremitus in the right hemithorax. Percussion was hyperresonant and dull over the medial aspect of the right hemithorax. On auscultation, vesicular breath sounds were present bilaterally (+/+), with additional rhonchi noted (+/+) but no wheezing (-/-). Cardiac sounds I/II were pure and regular, with no additional sounds. A chest X-ray revealed cloudy opacities across both lungs, with a distinct patch containing an air-fluid level in the right lung. The heart size was normal, both sinuses were clear, and the right diaphragm was well-defined, while the left diaphragm showed tenting. The skeletal structures appeared intact. The radiological impression was pneumonia, a right lung abscess, and old left-sided tuberculosis.